EVALUATION OF THE PERFORMANCE OF AEROTANKS DUE TO ADD-ON ATTACHED BIOCENOSIS - Oleynik, O. Y.; Airapetian, T. S.; Kurganska, S. M. (Science and Transport Progress, 2019)
Purpose. The research involves the implementation of comparative calculations to evaluate the performance of aerotanks with add-on attached biocenosis (biofilm). Methodology. For improving the performance of the aerotanks due to the introduction of an additional load with attached biocenosis (biofilm), the authors constructed the mathematical models that consider the simultaneous oxidation of organic pollutants with suspended and attached biocenosis. Based on these models, the methods were developed for calculating clarification parameters. The authors performed evaluation of the influence of various clarification factors in aerotanks. They proved that the clarification intensity is increased due to additional elements with the attached biocenosis. Herewith, possible technological and structural schemes of aerotanks were considered, when the loading elements (nozzles, screens, etc.) are located throughout the whole volume or more densely and compactly only in its individual sections. Findings. The parameters of effluent clarification from organic pollution in the aerotanks are determined using numerical methods. The graphs show the significant performance of aerotanks due to the introduction of the additional load with the attached biocenosis (biofilm). The calculations of the effect of additional loading on the performance of complete-mix aerotanks and continuous-flow aerotanks show that the use of immobilized biocenosis can improve the quality of removal of organic pollutants by 2-5 times. Originality. The authors substantiated scientifically the influence of various factors of wastewater treatment in aerotanks, the efficiency of which is increased due to additional elements with the attached biocenosis. Practical value. The introduction of research results in wastewater treatment plants can significantly improve the quality of the removal of organic pollutants by biological methods. The implementation of the calculation methods for the proposed dependencies makes it possible to more fully and reasonably take into account important processes that significantly affect the utilization of organic pollutants and the efficiency of the aerotanks with the additional involvement of wastewater treatment by the attached biocenosis.